Pengaruh Akupresur Titik P6 Terhadap Mual Muntah Lambat Akibat Kemoterapi Pada Anak Usia Sekolah Dengan Leukemia Limfoblasitik Akut - Tri Budi, Utami (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Acupressure is one of the complementary therapy on children who are experience delayed chemotherapy-induced nausea and vomiting. Nausea vomiting is an effect that cause stress in children. The purpose of this ressearch was to determine the effect of acupressure P6 to delayed chemotherapy-induced nausea and vomiting in school-aged children with acute lymphoblastic leukemia in sanglah hospital. This study was a pre-experimental (one-group pre-post-test design). Sample consisted of 17 school children obtained from consecutive sampling. All respondent had been given acupressure with 30 times during 3 minute, it’s replay until total time is 15 minute. Before being given acupressure 13 (76,5%) chidren with severe nausea and vomiting, 4 (23,5%) chidren with moderate nausea and vomiting, and no chidren with low nausea and vomiting. After being given acupressure 12 (70,6%) chidren with low nausea and vomiting, 5 (29,4%) chidren with moderate nausea and vomiting, and no chidren with severe nausea and vomiting. Based on the Wilcoxon Signed Rank Test, this difference was statistically significant, with p value 0,000 ( p ?0,05), which mean there is an influence of acupressure P6 to delayed chemotherapy-induced nausea and vomiting in school-aged children with acute lymphoblastic leukemia in Sanglah hospital. The conclusion of the research was the acupressure can be applied as a non-pharmacological therapy to reduce nausea and vomiting caused by chemotherapy in children. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: school-aged children; acupressure; nausea and vomiting; acute lymphoblastic leukemia